2012
DOI: 10.1007/s00436-012-3109-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Azadirachta indica extract against Eimeria papillata-induced coccidiosis

Abstract: Coccidiosis in poultry is caused by protozoan parasites of the genus Eimeria, which is responsible for worldwide economic losses. The methanolic extract of Azadirachta indica (neem) leaves was used in vivo for its pharmacological, antioxidant, and anticoccidial properties. Four groups of mice were investigated. The first group was inoculated only with sterile saline and served as the control group. The second group was treated by oral gavage with neem extract (500 mg/kg) daily for 4 days. The third and fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 32 publications
8
38
0
Order By: Relevance
“…Currently, new trends have been developed to identify various dietary supplements of natural origin into feeding programs to control Eimeria infections (Dalloul et al 2003;Jang et al 2007;Molan et al 2009;Abbas et al 2010;Metwaly et al 2012a;Zhang et al 2012a,b;Dkhil et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, new trends have been developed to identify various dietary supplements of natural origin into feeding programs to control Eimeria infections (Dalloul et al 2003;Jang et al 2007;Molan et al 2009;Abbas et al 2010;Metwaly et al 2012a;Zhang et al 2012a,b;Dkhil et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…There is minimal evaporation through skin without accumulation; therefore, N 2 O is an ideal inhaled anesthetic (17). As anesthesia performance of N 2 Ois low and weak, a high concentration of single use may cause anoxia; thus, its concentration should not be higher than 60% (18). We found that NF-κB of p65 and IL-6, caspase-3 and 9 activities in the isoflurane + N 2 O inhalation group were suppressed, compared with the propofol + fentanyl anesthesia group.…”
Section: Discussionmentioning
confidence: 99%
“…Non significant change in these parameters in groups vaccinated against NDV vaccine only, administered neem leaves aqueous extract only, or received both of them indicate no adverse effect of vaccination and neem extract constituents on the renal functions. Broiler chickens group which infected with NDV plus administration of neem leaves aqueous extract showed significant increasing in same parameters, but with lesser degree may be due to renal protective activity of neem leaves extract (Singh et al, 2014) as it is rich in flavonoids (rutin, quercetin, flavonoglycosides, polyphenols, and tannins) which play a vital role in protection against renal injury via anti-inflammatory and antioxidant activities (scavenging free radicals) (Dkhil et al, 2013;Kitdamrongtham et al, 2014) beside its potential anti-viral activity. These results were confirmed by histopathological changes of kidney, which showing congestion (Arrow) and focal haemorrhage (Arrowheads) (Fig.…”
Section: Discussionmentioning
confidence: 99%